Profile of Student Basic Teaching Skills through Online Learning Model Using Peer Assessment on Microteaching Lectures - Ika Nurani Dewi; Sumarjan Sumarjan (Universitas Muhammadiyah Sidoarjo, 2021)
The purpose of this study was to determine the profile of the basic teaching skills of biology education students during microteaching lectures through an online learning model using peer assessment. This type of research is a qualitative descriptive study. The subjects of this study consisted of 17 biology education students in the 6th semester of the 2019/2020 academic year. The technique of collecting data through observation uses a research instrument in the form of a rubric for assessing basic teaching skills, which is filled by lecturers and peers. Data analysis techniques include data reduction, data display and conclusions. The observed teaching skill indicators consist of 8 components. Based on these 8 indicators, the results obtained are the skills of opening and closing learning, explaining skills, questioning skills, discussion guiding skills, and class management skills are in the skilled category, the skills to provide reinforcement and the skills to make variations are in the fairly skilled category, while the skills to use learning media are in the less skilled category. Overall, the basic teaching skills of biology education students have improved during the microetaching exercise using peer assessment.